Transcriptomes That Confer to Plant Defense against Powdery Mildew Disease in Lagerstroemia indica - Xinwang Wang; Weibing Shi; Timothy Rinehart (International Journal of Genomics)
Transcriptome analysis was conducted in two popular Lagerstroemia cultivars: “Natchez” (NAT), a white flower and powdery mildew resistant interspecific hybrid and “Carolina Beauty” (CAB), a red flower and powdery mildew susceptible L. indica cultivar. RNA-seq reads were generated from Erysiphe australiana infected leaves and de novo assembled. A total of 37,035 unigenes from 224,443 assembled contigs in both genotypes were identified. Approximately 85% of these unigenes have known function. Of them, 475 KEGG genes were found significantly different between the two genotypes. Five of the top ten differentially expressed genes (DEGs) involved in the biosynthesis of secondary metabolites (plant defense) and four in flavonoid biosynthesis pathway (antioxidant activities or flower coloration). Furthermore, 5 of the 12 assembled unigenes in benzoxazinoid biosynthesis and 7 of 11 in flavonoid biosynthesis showed higher transcript abundance in NAT. The relative abundance of transcripts for 16 candidate DEGs (9 from CAB and 7 from NAT) detected by qRT-PCR showed general agreement with the abundances of the assembled transcripts in NAT. This study provided the first transcriptome analyses in L. indica. The differential transcript abundance between two genotypes indicates that it is possible to identify candidate genes that are associated with the plant defenses or flower coloration.